2017
DOI: 10.1111/jeb.13075
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of antigenic diversity in the tick‐transmitted bacterium Borrelia afzelii: a role for host specialization?

Abstract: Antigenic diversity in pathogenic microbes can be a result of at least three different processes: diversifying selection by acquired immunity, host-pathogen coevolution and/or host specialization. Here, we investigate whether host specialization drives diversity at ospC (which encodes an immunodominant surface protein) in the tick-transmitted bacterium Borrelia afzelii. We determined prevalence and infection intensity of ospC strains in naturally infected wild mammals (rodents and shrews) by 454 amplicon seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Our work on a wild population of I. ricinus in Neuchâtel, Switzerland found that approximately 80% of nymphs infected with B. afzelii carried more than one strain [42,44]. In the present study, the rodents were infected with a maximum of two strains whereas in the field, rodents are often infected with more than two strains [10,29,54]. These differences in strain richness in the rodent host explain why the percentage of co-infected nymphs in our experiment (43.7%) was lower than what we have observed in nature.…”
Section: Discussionmentioning
confidence: 44%
“…Our work on a wild population of I. ricinus in Neuchâtel, Switzerland found that approximately 80% of nymphs infected with B. afzelii carried more than one strain [42,44]. In the present study, the rodents were infected with a maximum of two strains whereas in the field, rodents are often infected with more than two strains [10,29,54]. These differences in strain richness in the rodent host explain why the percentage of co-infected nymphs in our experiment (43.7%) was lower than what we have observed in nature.…”
Section: Discussionmentioning
confidence: 44%
“…The uniform distribution of B. garinii STs among ticks collected from various bird species, and other sources (e.g., questing ticks), does not suggest specialization of certain B. garinii STs to certain hosts, contrary to the hypothesis of multiple niche polymorphism associated with OspC variation (Brisson, Drecktrah, Eggers, & Samuels, ) found for B. burgdorferi sensu stricto (Brisson & Dykhuizen, ; Vuong et al, ), but not for B. afzelii (Raberg et al, ). Our results are consistent with birds being the main reservoir hosts of B. garinii : they maintain its natural transmission cycle and are the source of infection for questing vector ticks.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, there may be ‘general’ drivers of tick-borne diseases that operate directly through the shared tick vector, as well as ‘specific’ drivers that are associated with the dynamics and distributions of the various reservoir hosts of the pathogen. In Europe, the most common pathogen that causes Lyme disease is Borrelia afzelii , which has a small mammal reservoir 24 27 ; less common are B. garinii (in birds) and B. burgdorferi sensu stricto (a generalist). A. phagocytophilum has a wide range of reservoir hosts in Europe including wild ruminants, rodents, insectivores, birds, carnivores, and domestic animals 28 .…”
Section: Introductionmentioning
confidence: 99%